Design and Implementation of an Integrated Network Management System Based on Principal Component Analysis - Xiangyun Kong; Tienan Chu (Dianxin kexue)
In the big data era, efficient using of data has become an important factor in determining the competitiveness of operators. Currently the main method for network operators in data analysis is OLAP based on data warehouse. As the performance of OLAP analysis relies heavily on pre-defined data model, it's difficult for the system track the real-time changes of wireless network, which cause the current network management system always doesn't meet the actual needs of operators. A method to solve the above mentioned problem based on principal component analysis was presented, and the implementation example and the comparison of the method were given.